Methods for obtaining body temperature of infant dairy calves - Bertipaglia, Liandra Maria Abaker; Melo, Gabriel Maurício Peruca de; Melo, Wanderley José de; Cardim, Laís; Lima, Caroline Fernanda Franco de; Quilis, Amanda Bertipaglia; Moitinho, Aurélio Marcos dos Santos (Seven Editora, 2023)
The aim of the present study was to evaluate noninvasive methods of body temperature determination as an alternative to the conventional method (rectal temperature) in lactating dairy calves. The study used rectal temperature measurements, obtained with digital contact thermometer, which were considered in the present study as a reference of body and physiological temperature in the comparison of the temperature of the forehead, pinna, back and vulva, obtained with the digital infrared thermometer with laser sight and with the thermographic camera. The main hypothesis of the study was that an image taken with a thermographic camera can be used as a non-invasive technique to replace the infrared thermometer (non-invasive) and the conventional digital contact thermometer (invasive) in recording the body temperature of infant Holstein calves. According to the results observed in the comparison of means, the highest temperature was the rectal temperature evaluated with the digital thermometer and significantly different from the others (p<0.05) and the method that came closest to the physiological value, but with significant difference, was the thermographic camera (CT) in the evaluation of vulva temperature. In Pearson's linear correlation analysis, the rectal temperature data and the thermographic camera of the pinna were the ones that presented the highest linear correlation, that is, physiological changes were more responsive. It is concluded that less invasive alternative methods are promising techniques, however, they do not replace the obtaining of rectal temperature to diagnose deviations from the normal physiological condition of the calves. DOI:https://doi.org/10.56238/uniknowindevolp-081